Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Daya Listrik Rumah Tangga (Studi Kasus Pada Perumahan Griya Bangko Asri, Kabupaten Merangin) - Erwita Pujiastuti (e-Journal Perdagangan Industri dan Moneter, 2017)
The amount of power that can be chosen by the consumer households based on household tariff group R1 / power which is equal to 450 VA, 900VA, 1300 VA and 2200 VA. Electricity demand is not only due to the increasing use of electricity by customers, technological developments also encourage the emergence of new products that use electricity. Based on these problems the author considers it necessary to make a study entitled Analysis of Factors Affecting Demand Household Electricity (Case study Bangko Griya Asri, Merangin District). The factors studied were the number of income, number of family aggota, building houses, energy expenditure and the level of education of the respondents. Based on the analysis obtained, the variables that affect the demand for household electrical power is a variable amount of income, number of family members, building houses, energy expenditure